Active Child, Healthy Child Project: The Effects on Dynamic Balance of an Increase in Femoral Anteversion in Healthy Developing Children - APTİ, ADNAN; AKALAN, NAZİF EKİN; AKEL, BURCU SEMİN; EVRENDİLEK, HALENUR; ÖNERGE, KÜBRA; NAS, İMGE (AVES, 2024)
Objective: Increased femoral anteversion (IFA) is defined as the anterior rotation of the femoral head in relation to the transcondylar axis of the knee. The aim of this study was to determine the frequency of IFA in healthy developing children and to investigate the effects of IFA on dynamic balance. Methods: School screening was conducted on 315 school-age children (6-14 years old, mean 9.9 ± 2 years), and IFA was determined in 26 children. From the same sample, 36 children with no IFA were selected as the control group. Data obtained from the Y balance test, handgrip strength with a digital dynamometer, IFA according to the Craig’s test, and joint hypermobility according to the Beighton score were compared between the groups. Independent sample t-test and Pearson’s correlation test were used in the statistical analysis. Results: This study was carried out on a narrow universe of children mean aged 9.9 ± 2 years, and the incidence of IFA was determined as 8.3%. The Y balance scores were found to be higher in the IFA group than in the controls (P=.049 right, P=.027 left). There was no correlation between Craig’s test and the Y balance test results (r=0.04). No difference was found between the groups for muscle strength and joint hypermobility scores associated with balance. Conclusion: Balance may not be one of the causes of frequent falls in children with IFA. Further studies are needed to further examine the biomechanical causes of falls, as studies to improve balance may not provide sufficient benefit to prevent fall-related trauma and injury in children with IFA. © 2024 AVES. All rights reserved.
Keywords: Balance; Increased Femoral Anteversion; Joint Hypermobility; Muscle Strength